ЗАВИСИМОСТЬ СТРУКТУРЫ ЗОН ПОЛУПРОВОДНИКОВ ОТ СКОРОСТИ РЕКОМБИНАЦИИ МЕЖДУ ЗОНАМИ (World Science, 2020)
This article researches the dependence of recombination processes that occur in semiconductors on the structure of semiconductor zones. The advantages of using faulty zonal semiconductors in the development of solar cells have been substantiated.